Les narcocorridos du Movimiento Alterado : une poésie de la rue ? - Claude Chastagner (Les Cahiers de Framespa)
This article explores the most recent development of the narcocorrido tradition, the very successful Movimiento Alterado. Mexican-American artists such as El Komander use polka or waltz tunes to describe in violent and explicit words the daily lives of drug lords. Most artists and record companies are located in California, from where the style is exported to Mexico. The present article deals with the roots of these corridos, the various interpretations that can be suggested, before wondering to what extent they can be considered as a form of street poetry.